2016
DOI: 10.1097/mph.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Year EFS of Multisystem LCH With Risk-Organ Involvement Is Suboptimal

Abstract: The study describes an 8-year experience of a single center in managing patients with langerhans cell histiocytosis on the basis of the langerhans cell histiocytosis-III platform. A retrospective case-file review of children diagnosed during 2006 to 2013 was performed. Group 1 (multisystem with risk-organ involvement) patients received an initial treatment of 6 to 12 weeks, followed by continuation treatment to complete 12 months. Drugs included vinblastine, prednisolone, and 6-mercaptopurine. Group 2 (multisy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…1 and 5), who had hypoalbuminemia and/or conjugated hyperbilirubinemia, but had disease progression and subsequently died from the disease. Conjugated hyperbilirubinemia could be a sign of sclerosing cholangitis with greater mortality for MS-LCH [ 12 , 38 ]. Braier et al [ 37 ] reported that hypoalbuminemia was associated with inferior prognosis in MS-LCH.…”
Section: Discussionmentioning
confidence: 99%
“…1 and 5), who had hypoalbuminemia and/or conjugated hyperbilirubinemia, but had disease progression and subsequently died from the disease. Conjugated hyperbilirubinemia could be a sign of sclerosing cholangitis with greater mortality for MS-LCH [ 12 , 38 ]. Braier et al [ 37 ] reported that hypoalbuminemia was associated with inferior prognosis in MS-LCH.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 LCH is classified as a single system disease (SS-LCH) or multisystem disease (MS-LCH), based on the extent of system involvement. Totadri et al 4 reported that patients with SS-LCH have favourable prognoses, while patients with MS-LCH have lower rates of either five-year event-free or overall survival, particularly those with risk-organ involvement. MS-LCH involving risk organs, such as the central nervous system (CNS), haematopoietic system or liver, may lead to a rapidly fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has also reported that event-free survival for MS-LCH with risk organ involvement is suboptimal in Indian patients. [9] A couple of recent studies have reported good results in relapsed/refractory LCH and given new hope in this difficult subset of patients. However, patients with refractory/progressive disease in our series had adverse outcome.…”
Section: Discussionmentioning
confidence: 99%